From a 'necessary evil' to an art of contingency : Michael Oakeshott's conception of political activity in British postwar political thought - Soininen, Suvi (2003)
The aim of this study is to contribute to the understanding of the change in Michael Oakeshott' s conception of political activity in the context of British postwar political thought. This is done by examining the shifts and nuances in Oakeshott's production and by relating them to other contemporary thought. No specific method is applied, but the philosophical presuppositions of the 'Cambridge school of history' are largely shared. The main thesis is that Oakeshott' s notion of political activity shifted from an early near despise towards a laudation of political activity in his late production. It is also argued that many of Oakeshott's central concepts, such as authority, power and tradition, were also altered accordingly during the period after the Second World War. The study also argues for a closer relationship between Oakeshott' s thought and its contemporary context than is usually conceived: Oakeshott is both seen as a modeller of discussion and responding to it by his own conceptualizations of political activity. This study also takes a stand towards a disputed question of Oakeshott's understanding of the practice/theory relationship and it is concluded that Oakeshott modified his account of the significance of political activity in the conversation of mankind. In this conversation of the modes or voices of experience/ civilization politics finally conversates in equal terms with philosophy.